Design and fabricationof the egg cleaning machine with the productivity 3000 pcs/hour - Tran , Thu Hà; Nguyen , Văn Bạn (Journal of Technical Education Science, 2016)
This paper presents a suggested technology process and block cleaning machine for eggs in small-scale production poultry farms in the country. This machine consists of key phases including: a conveyor for mechanical cleaningwith a water sprayer synchronized with brushes for washing impurities on eggshells; a drying and pasteurizing block, and code printers on eggs. This egg processing machine has been manufactured and tested to achieve a productivity of from 2950 to 3005 eggs per hour. With such productivity, this machine will help domestic companiessupply fresh eggs to consumers with competitive costs.